Computational fluid dynamics analysis of savonius wind turbine at varying twist angles - Ubando, Aristotle T. (February 2009)
One of the vital steps in designing a wind turbine system is the evaluation of its torque characteristics which are evaluated using wind tunnel testing. However, wind tunnel testing is expensive and time consuming method especially if varied design configurations are to be considered. The study aims to establish an alternative approach in evaluating torque characteristics of a Savonius wind turbine using a computational fluid dynamic approach employing finite volume method. It establishes a validation process in evaluating the effects of the four most common two equation turbulence models and assess the impact of two varying computational domain size. The modeling assumptions used were validated using a recent result of a wind tunnel experiment by Hayashi et al. The study also utilized Simpson?s rule of numerical integration in averaging the torque coefficient. Results show that the use of an appropriate turbulence model is the primary determining factor in getting numerical results in comparable with a wind tunnel experiment. Furthermore, with the modeling strategy established, results of the twisted blade Savonius rotor with twist angles of 20 degrees, 40 degrees, 60 degrees and 90 degrees were evaluated and compared with the selected baseline data from the previously established models. The results illustrate different trends of the torque coefficient at different twist angles and also indicate that at a certain twist angle, a maximum average torque coefficient is achieved.
Thesis (M.S. in Mechanical Engineering)--University of the Philippines Diliman.
Keywords: Wind turbines